Physical activity and risk of cognitive decline: a meta‐analysis of prospective studies - Sofi, F.; Valecchi, D.; Bacci, D.; Abbate, R.; Gensini, G. F.; Casini, A.; Macchi, C. (Journal of internal medicine, 2011)
.  Sofi F, Valecchi D, Bacci D, Abbate R, Gensini GF, Casini A, Macchi C (Centro S. Maria agli Ulivi, Onlus IRCCS; Thrombosis Centre, University of Florence; Azienda Ospedaliero‐Universitaria Careggi, Florence, Italy) Physical activity and risk of cognitive decline: a meta‐analysis of prospective studies. J Intern Med 2011; 269: 107–117. Objective.  The relationship between physical activity and cognitive function is intriguing but controversial. We performed a systematic meta‐analysis of all the available prospective studies that investigated the association between physical activity and risk of cognitive decline in nondemented subjects. Methods.  We conducted an electronic literature search through MedLine, Embase, Google Scholar, Web of Science, The Cochrane Library and bibliographies of retrieved articles up to January 2010. Studies were included if they analysed prospectively the association between physical activity and cognitive decline in nondemented subjects. Results.  After the review process, 15 prospective studies (12 cohorts) were included in the final analysis. These studies included 33 816 nondemented subjects followed for 1–12 years. A total of 3210 patients showed cognitive decline during the follow‐up. The cumulative analysis for all the studies under a random‐effects model showed that subjects who performed a high level of physical activity were significantly protected (−38%) against cognitive decline during the follow‐up (hazard ratio (HR) 0.62, 95% confidence interval (CI) 0.54–0.70; P < 0.00001). Furthermore, even analysis of low‐to‐moderate level exercise also showed a significant protection (−35%) against cognitive impairment (HR 0.65, 95% CI 0.57–0.75; P < 0.00001). Conclusion.  This is the first meta‐analysis to evaluate the role of physical activity on cognitive decline amongst nondemented subjects. The present results suggest a significant and consistent protection for all levels of physical activity against the occurrence of cognitive decline.